Elif's seoulitude - Tenzin Tsetan Choklay; Han'guk Yŏnghwa Ak'ademi. (Honolulu, HI : Korean Academy of Film Arts (KAFA), 2008)
Elif has just arrived in Seoul to visit her boyfriend, but is disturbed when her boyfriend turns out to be uncontactable. Deciding to wait a few days, Elif goes about exploring the tourist attractions of Seoul and befriends tourist guide, Nam-hyeon.
Title from resource description page (viewed June 19, 2014).
Electronic reproduction.
This edition Korean and English.
Keywords: Man-woman relationships -- East Asia -- Drama; Short films; Man-woman relationships; Drama; Fiction films; Short films